Comparison of demineralization around orthodontic brackets cured by conventional method and transillumination technique-an in vitro evaluation - Monis Raza; Piush Kumar; Nikita Gulati; Payal Sharma; Divya Shetty; Devicharan Shetty (Wolters Kluwer Medknow Publications, 2020)
OBJECTIVE: To compare demineralization around orthodontic brackets cured by conventional method and transillumination method. MATERIALS AND METHOD: Sixty freshly extracted human premolar teeth were divided into four groups. Group 1: Brackets bonded with conventional method of bonding by curing labially for 40 sec. Group 2: Brackets bonded with transillumination method of bonding for 50 sec. Group 3: Brackets bonded with conventional method of bonding by curing labially for 20 sec followed by 30 sec of transillumination. Group 4: Brackets bonded with transillumination method of bonding for 30 sec followed by labial curing for 20 sec. Ground sections were prepared of each tooth and microleakage was evaluated using a binocular microscope at 40× magnification (Olympus BX53) and an image was taken using a digital camera (Olympus EPL3) connected to the microscope. The images were analyzed using Magnus Pro Image software. Scores were assigned to different degrees of microleakage at the demineralization zone around enamel-adhesive-bracket complex at the occlusal, middle, and gingival margins using linear measurement tool. Data obtained was subjected to statistical analysis using SPSS software (Version 20.0). Level of significance was kept at 5%. Intragroup comparison was done using Kruskal-Wallis test followed by Mann-Whitney U-tests for pairwise comparison. RESULTS: Group 4 showed least mean demineralization in occlusal, middle, and cervical areas as compared to other groups and the results were statistically significant (P < 0.05). CONCLUSION: Transillumination can be employed as a method synergistically with conventional curing to achieve minimum amount of demineralization during fixed orthodontic treatment.